Should Economists Make Value Judgments? - Black, John D. (Quarterly Journal of Economics, 1953)
Journal Article Should Economists make Value Judgments? Get access John D. Black John D. Black Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 67, Issue 2, May 1953, Pages 286–297, https://doi.org/10.2307/1885340 Published: 01 May 1953